(untitled) (Atlas Journal of Biology, 2024)
The rhizosphere represents the main source of bacteria commonly referred to as rhizobacteria. Such beneficial rhizobacteria with plant-beneficial activities are generally defined as plant growth promoting rhizobacteria (PGPR). The aim of this study was to investigate the ability of native rhizobacteria (PGPR) isolated from an arid soil of date palm in Al-Qassim region, Saudi Arabia, to enhance plants growth. Maize (Zea mays L.) was used as model crop for this research. Maize seedlings roots were inoculated with Bacillus and Enterobacter bacteria. The seedlings showed significant increases in stem, leaf, and root growth. The maximal shoot lengths were obtained with strain (I2: Bacillus cereus) (95.41 cm) with an increase of 33.45 % compared to uninoculated control seedlings. The three isolates I2: Bacillus cereus, AZS2: Bacillus subtilis and commercial strain AZB: Azospirillum brasilense) caused a highly significant increase in the total number of leaves ranging from 10.9% to 12.7% compared to the uninoculated controls. Seedlings inoculated with AZS2: Bacillus subtilis strain exhibited the highest aerial dry biomasses with an improvement of more than 85 % (30.76 g) compared with uninoculated control plants and more than 62 % compared to uninoculated NaCl control plants. The inoculation treatment with I2: Bacillus cereus strain induced an improvement of more than 65 % (27.44 g) over uninoculated control and more than 45 % over uninoculated NaCl control. The strain AZS2: Bacillus subtilis produced the highest root dry weights, in comparison to other isolates and induced an improvement of 30.17% (26.06 g) compared to uninoculated control plants and 24.09% compared to uninoculated plants (NaCl control).The most effective rhizobacterial treatment in the dry biomasses of whole seedling (aerial dry biomass and root dry biomass) is AZS2: Bacillus subtilis strain which induced an improvement of 55% (56.83 g) compared to uninoculated plants and 42% compared to uninoculated plants (NaCl-control)...